Based on Systematic Pharmacology: Molecular Mechanism of Siwei Jianbu Decoction in Preventing Oxaliplatin-Induced Peripheral Neuropathy. (6th October 2020) - Zhang, Peng; Lu, Yuting; Yang, Chao; Zhang, Qiuyan; Qian, Yangyan; Suo, Jinshuai; Cheng, Peng; Zhu, Jing
Abstract : Chemotherapy-induced peripheral neuropathy (CIPN) is a dose-limiting side effect caused by chemotherapy drugs, and its existence seriously affects the quality of life of patients. We first established an oxaliplatin-induced peripheral neuropathy (OIPN) model and then measured and evaluated mechanical hyperalgesia, thermal nociception, cold allodynia, and intraepidermal nerve fiber (IENF) density to determine Siwei Jianbu Decoction's role in preventing OIPN. Then, we conducted a systematic pharmacological study that revealed important roles for the MAPK signaling pathway and proinflammatory immune pathway and confirmed these roles by western blot, immunofluorescence, and qPCR. The data show that Siwei Jianbu Decoction can effectively prevent oxaliplatin-induced neuroinflammation by inhibiting an increase in NF- κ B expression via downregulation of p-ERK1/2 and p-p38. The present study showed that SWJB may be beneficial in preventing oxaliplatin-induced peripheral neuropathy.